The Effect of Modified Media Target Practice Goal Equipment in Improving Petanque Shooting Ability - Soemardiawan, Soemardiawan; Yundarwati, Susi (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
the problem is that many athletes whose shooting technique is still not perfect, meaning the ball often falls long before the target ball. Apart from that, many also have a low level of accuracy. The aim of the research is to find out the influence of media modification of target practice tools on improving pétanque shooting ability. The research method uses one group pretest–posttest design. With a sample of 7 DL UNDIKMA athletes, the instrument used was the pétanque shooting test. From the data above, it can be described that the shooting ability of DL UNDIKMA petanque athletes when the pretest data was taken was with an average of 4.7143, a middle value of 3, a frequently occurring value of 0 and a standard deviation of 4.8892. Meanwhile, the highest score was 14 and the lowest score was 0. The shooting ability of DL UNDIKMA petanque athletes when collecting posttest data was with an average of 13.0000, a middle value of 12, a frequently occurring value of 11, and a standard deviation of 2.7080. that there has been a significant increase.